2021
DOI: 10.3390/ijerph18136994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Primary, Secondary Stability, Bone Density, Percentage of Vital Bone Formation and Implant Size

Abstract: Background: This study aims to evaluate whether there is a correlation between implant stability, bone density, vital bone formation and implant diameter and length. Methods: Ninety patients were enrolled in this study. They underwent a socket preservation procedure with allograft or PRF and after 4 months, a total of 90 implants were placed. CBCT scans were assigned prior to implant placement in order to assess the bone density. During the surgical re-entry, a bone biopsy was harvested with a trephine drill. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…29 A plausible explanation for this observation is that wider DI would be more stable than narrower ones because they can potentially engage a larger amount of the osseo-integrated interface. On the other hand, other studies, 37,38 found no difference regarding the effect of DI diameter on secondary stability ISQ values.…”
Section: Discussionmentioning
confidence: 70%
“…29 A plausible explanation for this observation is that wider DI would be more stable than narrower ones because they can potentially engage a larger amount of the osseo-integrated interface. On the other hand, other studies, 37,38 found no difference regarding the effect of DI diameter on secondary stability ISQ values.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, Vasilena Ivanova et al [33] reported a positive correlation between secondary stability and bone density (r = 0.498). They underwent a socket preservation procedure with allograft or platelet-rich fibrin (PRF) and after 4 months, a total of 90 implants were placed.…”
Section: Discussionmentioning
confidence: 79%
“…In our research, the grafting material was completely absorbable, so it was not affecting the measurements [50]. Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55]. Nevertheless, the literature data on those correlations are ambiguous, which has to be taken into consideration when drawing conclusions [50].…”
Section: Discussionmentioning
confidence: 79%